2022
DOI: 10.1055/a-1903-1943
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Nutritional Risk Index as a Prognostic Factor of Patients with Non-Small Cell Lung Cancer: A Meta-Analysis

Abstract: Geriatric nutritional risk index (GNRI), a newly developed indicator of nutritional status retrieved by serum albumin concentration and ideal body weight, has been suggested as a prognostic factor for various malignancies. The aim of the study was to summarize the prognostic role of GNRI for patients with non-small cell lung cancer (NSCLC) in a meta-analysis. Cohort studies evaluating the relationship between GN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Recent meta-analyses have reported that the GNRI significantly predicts cancer prognosis (34)(35)(36)(37)(38). Zhang et al conducted a meta-…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses have reported that the GNRI significantly predicts cancer prognosis (34)(35)(36)(37)(38). Zhang et al conducted a meta-…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it can also be used as a parameter for determining drug discontinuation and other reductions in treatment efficiency. In contrast, neutrophilto-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), Geriatric Nutritional Risk Index (GNRI), and Prognostic Nutritional Index (PNI) have been reported to affect TKI survival and adverse effects (10)(11)(12)(13). Therefore, appropriate nutritional assessment is important for therapy continuation.…”
mentioning
confidence: 99%
“…For elderly patients with heart failure, a meta-analysis of nine studies involving 7,659 patients revealed that low GNRI was predictive of all-cause mortality (HR: 1.56) compared to high GNRI (62). In addition, low GNRI values have been associated with an increased overall mortality risk in patients with head and neck, gastrointestinal, or lung cancer, with HRs ranging from 2.39 2.84 (63)(64)(65). Considering our findings and previous research, it appears that using the GNRI as a prognostic tool in patients on hemodialysis or suffering from cancer is more beneficial than in other clinical situations.…”
Section: Discussionmentioning
confidence: 99%